2018
DOI: 10.1111/jocd.12731
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approaches to axillary osmidrosis treatment: A comparison between superficial liposuction with automatic shaver curettage, subcutaneous laser treatment, and microwave‐based therapy with a modified technique

Abstract: Comparing to other treatments, microwave-based therapy was effective in treating osmidrosis with minimal downtime, recurrence, and complications. It could be a durable and effective therapeutic modality for osmidrosis and is less operator-dependent. It may be considered as a first-line treatment for axillary osmidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 25 publications
2
36
1
Order By: Relevance
“…Treatment methods include en bloc excision of the skin and subcutaneous tissue, suction curettage, shaving the subcutaneous sweat glands manually with or without carbon dioxide vaporization, and selective surgical excision of apocrine and eccrine glands [1]. More recently, various other methods, such as microwave-based therapy, percutaneous ethanol injection, and Versajet-assisted hydraulic epilation, have also been introduced [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment methods include en bloc excision of the skin and subcutaneous tissue, suction curettage, shaving the subcutaneous sweat glands manually with or without carbon dioxide vaporization, and selective surgical excision of apocrine and eccrine glands [1]. More recently, various other methods, such as microwave-based therapy, percutaneous ethanol injection, and Versajet-assisted hydraulic epilation, have also been introduced [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Though 80% of patients displayed subjective symptom improvement as assessed by doctors and nurses in our study, all patients reported symptomatic improvement after surgery. We evaluated the degree of odor using a 4-point scale, whereas other reports have evaluated degree of odor using a 10-point scale [3]. If we had evaluated degree of odor in the same way as those other reports, all patients would have shown a postoperative improvement in degree of odor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [24] compared laser coagulation and suction curettage, and concluded that suction curettage produced a higher incidence of complications than laser coagulation, but was more effective than laser coagulation. Yang et al [5] recently compared the outcomes of microwave coagulation, suction curettage, and laser coagulation. They concluded that microwave coagulation and suction curettage were superior to laser coagulation, but the complication rate of suction curettage was much higher than the rates of the other two procedures.…”
Section: Previously Reported Cohortsmentioning
confidence: 99%
“…Nonsurgical treatments include the use of topical deodorant, subcutaneous injection of botulinum toxin-A, and endoscopic thoracic sympathectomy. Surgical treatments include laser technology, axillary skin excision, suction curettage, and conventional open excision of apocrine glands [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%